The Growth Rates of Swedish Multinational Corporations - Sanden, Peter; Vahlne, Jan-Erik (Journal of International Business Studies, 1974)
The aim of this study was to examine the growth rates of Swedish multinational corporations. An attempt was made to answer the question of whether the MNCs have grown faster than has the Swedish manufacturing industry and, if so, to investigate the extent to which this can be explained by differences in multinationality. In order to separate the effect of that factor, technology-intensity, size, and profitability were included in the model; according to theory, these factors are correlated with multinationality and possibly with rates of growth.